Inhibitory effect of sterigmatocystin and 5,6-dimethoxysterigmatocystin on ATP synthesis in mitochondria. - Kawai, K (1984)
The inhibitory effects of sterigmatocystin, O-methylsterigmatocystin, and 5,6-dimethoxysterigmatocystin on the ATP synthesis system in mitochondria were compared with that of aflatoxin B1, which disturbs the respiratory chain in mitochondria. Sterigmatocystin and 5,6-dimethoxysterigmatocystin were found to uncouple the oxidative phosphorylation process without causing depression of state 3 respiration. O-Methylsterigmatocystin did not exhibit uncoupling activity at the limited concentrations tested (due to its low solubility in an aqueous system). These compounds, as well as aflatoxin B1, elicited neither pseudo-energized nor energized swelling of mitochondria and did not inhibit Ca2+-induced swelling of mitochondria.